2015
DOI: 10.1002/cncy.21506
|View full text |Cite
|
Sign up to set email alerts
|

Cytomorphologic features that distinguish schwannoma from other low‐grade spindle cell lesions

Abstract: BACKGROUND: Fine-needle aspiration biopsy of spindled mesenchymal lesions, including schwannomas, are challenging because of overlapping cytomorphological features. The objective of the current study was to identify key diagnostic cytological criteria for the diagnosis of schwannoma and to distinguish it from its common mimics. METHODS: A total of 58 schwannomas were evaluated and compared with 98 benign and low-grade spindle cell lesions, including 17 gastrointestinal stromal tumors and 20 fibromatosis cases.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(55 citation statements)
references
References 35 publications
1
36
1
Order By: Relevance
“…The classical cytological features of schwannoma include tissue fragments with fibrillary stroma, wavy nuclei, Verocay bodies and intranuclear cytoplasmic inclusions. However, Chebib et al found that these features are not entirely specific for schwannoma. Intranuclear cytoplasmic inclusions may be seen in neurofibroma and LMS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The classical cytological features of schwannoma include tissue fragments with fibrillary stroma, wavy nuclei, Verocay bodies and intranuclear cytoplasmic inclusions. However, Chebib et al found that these features are not entirely specific for schwannoma. Intranuclear cytoplasmic inclusions may be seen in neurofibroma and LMS.…”
Section: Discussionmentioning
confidence: 99%
“…GIST is described in retroperitoneal location, but few case reports suggest its origin in pancreas. Presence of few epithelioid cells admixed with spindle cells along with absence of significant nuclear pleomorphism should raise a suspicion of GIST on morphology. Benign or malignant nature of GIST is based on size of tumour and mitotic count.…”
Section: Discussionmentioning
confidence: 99%
“…7,[22][23][24][25] Gastric schwannoma is an uncommon mesenchymal tumor characterized by spindle cell proliferation, which should be differentiated from other spindle cell tumors such as GIST and leiomyoma. Although the tumor cells of schwannoma, GIST and leiomyoma may have subtle differences in their cytomorphologic features, [11][12][13] the distinction of these entities primarily rest on the results of immunophenotypical analysis. Using a panel of immunostains including CD117, SMA, desmin, S100, and CD34 is often sufficient for their differential diagnosis.…”
Section: Case Reportmentioning
confidence: 99%
“…[5][6][7][8][9] Although the cytomorphologic features of schwannoma are well described, [10][11][12][13] there are only a few case reports of gastric schwannoma in the literature. [5][6][7][8][9] Although the cytomorphologic features of schwannoma are well described, [10][11][12][13] there are only a few case reports of gastric schwannoma in the literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation